PELAKSANAAN WARIS DI KECAMATAN ANGKOLA SANGKUNUR - ahmad sainul nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
In the division of inheritance, there is certainly a law that regulates inheritance, which is called inheritance law. The basic stipulation for the division of inheritance in Islamic law is that the share of men is 2:1 from the share of women, meaning that the share of men is more than that of women because they have more responsibilities. This provision applies from top to bottom or the oldest heir to the youngest heir.However, this is not practiced by the community in Angkola Sangkunur District, South Tapanuli Regency, the distribution of inheritance is different as described above for men 2:1 from the female share. The implementation of the distribution of inheritance that occurs in Angkola Sangkunur District, South Tapanuli Regency is based on the economic ability of the heirs with mutual consent. For this reason, researchers want to investigate further about how, reasons, and factors for implementing the distribution of inheritance based on economic considerations in Angkola Sangkunur District by using interview, observation and documentation techniques and then analyzing it descriptively because this research is field research.The result is the implementation of the distribution of inheritance in Angkola Sangkunur District, the first is the implementation of the distribution of inheritance according to Islamic law, the implementation of the division of inheritance based on a will, and the implementation of the division of inheritance based on customary law, namely based on economic considerations. The next factor is because of culture, there is no socialization and lack of individual awareness.